PENGARUH KUALITAS PEPELAYANAN DAN KINERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT (Keluarganya Warga Binaan Pemasyarakatan) PADA LEMBAGA PEMASYARAKATAN KELAS IIB SLAWI - Edi Sutrisno; Joko Mariyono (Multiplier: Jurnal Magister Manajemen, 2016)
This research is called the influence of the quality of services and performance employees to of community satisfaction his people residents under the jurisdiction of correctional in a correctional institution class IIB slawi. Based on a title in on the research aims to understand: 1. Know the influence of the quality of service for of community satisfaction his people residents under the jurisdiction of correctional in a correctional institution class iib slawi. 2. Know the influence of performance employees to of community satisfaction his people residents under the jurisdiction of correctional in a correctional institution class iib slawi. 3. Know the influence of the quality of services and performance employees to of community satisfaction his people residents under the jurisdiction of correctional in a correctional institution class IIB slawi. Research methodology used in this research is the method observation, interview, the questionnaire, and study literature, technique the sample non probability of sampling by using scale likert and methods the determination of sample used is convenience / accidental sampling as many as 171 sample.The method of analysis the data used is the method linear regression multiple ( multi linear regression ).The results of the study in partial shows that 1). The quality of services (x1) and performance employees (x2 in together have had a positive impact and significant impact on of community satisfaction his people residents under the jurisdiction of correctional) (y in a correctional institution class IIB Slawi. 2). The quality of services (x1 in partial have had a positive impact and significant impact on of community satisfaction his people residents under the jurisdiction of correctional) (y in a correctional institution class iib slawi. 3). Performance employees (x2 in partial have had a positive impact and significant impact on satisfaction masyarakan his people residents under the jurisdiction of correctional) (y in a correctional institution class IIB Slawi). Keyword: the quality of services , performance employees , of community satisfaction